The Extratropical Transition of Hurricane Debby (1982) and the Subsequent Development of an Intense Windstorm over Finland - Laurila, Terhi; Sinclair, Victoria; Gregow, Hilppa (Monthly Weather Review, 2020)
On 22 September 1982, an intense windstorm caused considerable damage in northern Finland. Local forecasters noted that this windstorm potentially was related to Hurricane Debby, a category 4 hurricane that occurred just 5 days earlier. Due to the unique nature of the event and lack of prior research, our aim is to document the synoptic sequence of events related to this storm using ERA-Interim reanalysis data, best track data, and output from OpenIFS simulations. During extratropical transition, the outflow from Debby resulted in a ridge building and an acceleration of the jet. Debby did not reintensify immediately in the midlatitudes despite the presence of an upper-level trough. Instead, ex-Debby propagated rapidly across the Atlantic as a diabatic Rossby wave-like feature. Simultaneously, an upper-level trough approached from the northeast and once ex-Debby moved ahead of this feature near the United Kingdom, rapid reintensification began. All OpenIFS forecasts diverged from reanalysis after only 2 days indicating intrinsic low predictability and strong sensitivities. Phasing between Hurricane Debby and the weak trough, and phasing of the upper- and lower-level potential vorticity anomalies near the United Kingdom was important in the evolution of ex-Debby. In the only OpenIFS simulation to correctly capture the phasing over the United Kingdom, stronger wind gusts were simulated over northern Finland than in any other simulation. Turbulent mixing behind the cold front, and convectively driven downdrafts in the warm sector, enhanced the wind gusts over Finland. To further improve understanding of this case, we suggest conducting research using an ensemble approach. Peer reviewed